MMP13 Polymorphism Decreases Risk for Dental Caries - Tannure, P.N.; Küchler, E.C.; Falagan-Lotsch, P.; Amorim, L.M.F.; Raggio Luiz, R.; Costa, M.C.; Vieira, A.R.; Granjeiro, J.M. (Caries research, 2012)
Recent evidence suggests that genetic studies may contribute to a better understanding of individual susceptibility to caries. Matrix metalloproteinases (MMPs) and their tissue inhibitors have been suggested to be involved in the caries process. The purpose of this study was to determine if polymorphisms in MMP2 (rs243865), MMP9 (rs17576), MMP13 (rs2252070), and TIMP2 (rs7501477) were associated with caries. Eligible unrelated children and adolescents were evaluated using a cross-sectional design. Data on oral health habits was obtained through a questionnaire and caries data was collected by clinical examination. Genotyping of the selected polymorphisms was carried out by real-time PCR. Allele and genotype frequencies were compared between individuals with and without caries experience. Of 505 subjects, 212 were caries-free and most subjects (61.2%) had mixed dentition. Allele frequency of MMP2, MMP13 and TIMP2 was different between caries-affected and caries-free individuals, with significant association for MMP13 (p = 0.004). Mutant allele carriers for MMP13 demonstrated a significantly decreased risk for caries (OR = 0.538, 95% CI 0.313–0.926); this result remained significant after adjustment for candidate genes, type of dentition and dietary factors. Allelic and genotype frequencies of the polymorphism in MMP9 were similar in caries-affected and caries-free individuals. Genetic variations in MMP13 may contribute to individual differences in caries susceptibility. Our findings reinforce that susceptibility to caries results from gene-environment interactions.